ЕMPATHY AS CONDITIONS OF HUMAN CREATIVITY - Tamara N. Matyukh (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
In the history of aesthetics the problem of art creativity long time hasn't realized by the greater part of researchers in total of all its structural elements. It formed a rather paradoxical situation, because definition of aesthetics is always a part of it, such as art and – simultaneously – the issue is no science that reveals the essence of the person who creates the art. The purpose of this article is to study empathy as a special manifestation of human sensibility in the process flow of the creative act that reveals the essence of the artist's creative activity, developed sensuality is transformed into a work of art. Methodological and theoretical basis of the study was a combination of systemic, structural-functional and hermeneutic approaches; psychological and philosophical concepts of empathy problems and theoretical analysis of foreign and domestic literature in the field of philosophy, aesthetics, psychology. The scientific novelty of the research results is determined by the subject of study. The problem of art itself is in the field of modern aesthetic science, but in the context of its consideration of empathy reveals new theoretical aspects that deepen the level of processing and correcting the problem. Conclusions. Empathy, being a particular manifestation of human sensibility, is a necessary condition for creativity. After analyzing the nature of human creativity we came to the conclusion that the basis of the embodiment of sensibility of the artist in a work of art is a process of empathy. It is noted that the method of empathy is one of heuristic methods of creative activity, which is based on a process of empathy, i.e. identification of the object and the subject of creativity, "use", and creator inherent in any field of activity and is widely used in solving problems of art.